Outcomes of genital hygiene and anxiety training for mothers of girls with profound intellectual disabilities: A randomized controlled experiment - Kaçan, Havva; Bayram Değer, Vasfiye; Sakız, Halis (Informa UK Limited, 2022)
Female children with profound intellectual disabilities (IDs) may experience symptoms of urinary tract infections (UTIs) and depend on others' care. However, their caregivers may lack general hygiene skills and experience heightened anxiety when their care is expected. This study reports outcome of a training that aims to enhance genital hygiene skills and decrease anxiety levels of mothers of girls diagnosed with profound ID. The study was conducted in a city located in Turkey in 2020. It was designed with a randomized controlled experimental approach based on a pre-test and post-test model with experimental and control groups. The sample consisted of 66 mothers of girls who were diagnosed with profound ID, did not have UTI but were at high risk of developing it. A 6-week program with 24 sessions was implemented. After the training, mothers in the experimental group changed the sanitary pad and the underwear during menstruation and gave their daughters a bath more frequently; had a higher knowledge of recognizing and preventing UTI symptoms and cleaning of the perineum area; and had significantly lower levels of anxiety. A carefully designed simulator-based training can enhance the knowledge and skills of mothers to recognize the UTI symptoms, apply their knowledge to prevent the symptoms and implement genital hygiene practices, which in turn have a positive effect on reducing their level of anxiety.
Keywords: anxiety; feminine care; Intellectual disabilities; menstrual care; randomized controlled experiment; urinary tract infection; 3. Good health